2002
DOI: 10.1021/es011448i
|View full text |Cite
|
Sign up to set email alerts
|

On-line Analysis of Urban Particulate Matter Focusing on Elevated Wintertime Aerosol Concentrations

Abstract: A 10-day winter sampling campaign was conducted in downtown Toronto for particulate matter (PM) air pollution in the fine (<2.5 microm) size range. An aerosol laser ablation mass spectrometer (LAMS), a tapered-element oscillating microbalance (TEOM), and an aerodynamic particle sizer (APS) were operated in parallel to characterize the PM on-line. In this study, the LAMS observed differences in the chemical composition between three separate episodes with higher PM2.5 mass and APS counts. LAMS results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 33 publications
(47 reference statements)
0
42
0
Order By: Relevance
“…Recent field observations have positively correlated episodic aerosol formation events with elevated concentrations of atmospheric amines. For example, Tan et al have found in one episodic event of elevated PM 2.5 in an urban environment that organic amines were evident in all the particulate (Tan et al, 2002). Similarly, in remote boreal forest studies, Mäkelä and coworkers (Mäkelä et al, 2001) found a strong positive correlation between new particle formation events and the concentration of dimethylammonium (the ionic component of dimethylamine).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recent field observations have positively correlated episodic aerosol formation events with elevated concentrations of atmospheric amines. For example, Tan et al have found in one episodic event of elevated PM 2.5 in an urban environment that organic amines were evident in all the particulate (Tan et al, 2002). Similarly, in remote boreal forest studies, Mäkelä and coworkers (Mäkelä et al, 2001) found a strong positive correlation between new particle formation events and the concentration of dimethylammonium (the ionic component of dimethylamine).…”
Section: Introductionmentioning
confidence: 91%
“…There is growing evidence that organic nitrogen, including amines and amine-derived compounds, may form a substantial fraction of the organic aerosol load as evidenced in recent field studies in remote (Mäkelä et al, 2001;Beddows et al, 2004), urban (McGregor and Anastasio, 2001;Simoneit et al, 2003;Angelino et al, 2001;Tan et al, 2002), and agricultural (McGregor and Anastasio, 2001;Angelino et al, 2001) regions, and in regions near extensive biomass burning (Decesari et al, 2006;Mace et al, 2003;Simoneit et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al (2002) suggested that the presence of the TMA within aqueous surface on particles would promote the accumulation of sulfate and nitrate (R2 and R3). TMA also has the potential to undergo gas phase acidebase reactions (R4) with gaseous acids (e.g., HCl, HNO 3 and H 2 SO 4 ) mimic ammonia to form inorganic salts (Angelino et al, 2001;Murphy et al, 2007).…”
Section: Possible Formation Mechanism Of Particulate Tmamentioning
confidence: 99%
“…[13,[18][19][20] De Haan et al [21,22] observed that reactions between glyoxal and amines or amino acids can produce light-absorbing, nitrogen-containing imidazoles and oligomers. Particle phase amines have been extensively observed in many areas [9,17,[23][24][25] especially in ultrafine particles during nucleation [26][27][28] and particle growth [29] events. Compared with ammonia, amines have higher molecular weights and present stronger alkalinity that make them perfect candidates in new particle formation and growth.…”
Section: Introductionmentioning
confidence: 99%